Characterization of the feeding behavior of three Erythroneura species on grapevine by histological and DC‐electrical penetration graph techniques. Issue 2 (3rd October 2015) - Saguez, Julien; Lemoyne, Pierre; Giordanengo, Philippe; Olivier, Chrystel; Lasnier, Jacques; Mauffette, Yves; Vincent, Charles
Abstract Feeding behavior of three leafhopper species – Erythroneura vitis (Harris), Erythroneura ziczac (Walsh), and Erythroneura elegantula (Say) (Hemiptera: Cicadellidae) – reared on grapevine, Vitis vinifera L. cv. 'Seyval blanc' (Vitaceae), was investigated using histological techniques and DC‐electrical penetration graphs (DC‐EPG). Histological studies revealed that the Erythroneura species induced white stipples on the leaves and that these leafhoppers produced thin salivary sheaths in grapevine leaf tissues. The DC‐EPG system allowed the characterization of five waveforms associated with stylet penetration and feeding in leaf tissues. These waveforms were characteristic of feeding phases corresponding to epidermis penetration pathway, salivation, and ingestion. We calculated 28 parameters (e.g., number of probes, duration of phases, and time spent in the various tissues) to describe and compare the feeding behavior of the Erythroneura species. We conclude that the three Erythroneura species are mainly mesophyll feeders but may probably also feed in other tissues such as xylem.